The effect of Medicago sativa extract and light on skin hypopigmentation disorders in C57/BL6 mice. (19th July 2022) - Ubaydee, Azal Hussein Najm; Issa, Reem; Hajleh, Maha N. Abu; Ghanim, Bayan Y.; Al‐Akayleh, Faisal; Qinna, Nidal A.
Abstract: Background: Vitiligo is a common depigmentation skin disease that affects the quality of life in many patients. Aims: This study aims to investigate the effect of Medicago sativa methanol extract on the treatment of skin hypopigmentation disorders. Methods: Antioxidant activity and phytochemical constituents of the extract were determined using DDPH assay, Folin–Ciocalteu, AlCl3, and HPLC‐MS/MS analysis. Oil in water (o/w) creams were prepared to contain the methanolic extract, and applied to hydroquinone‐induced depigmentation in vivo model and further challenged in combination with UVA light exposure. Skin and hair colors were visually scored and evaluated at different time intervals, and histopathological examinations of skin layers and hair follicles were performed. Results: A total phenolic content of 187.70 mg/g, equivalent to gallic acid, and total flavonoid content of 21.97 mg/g, equivalent to quercetin, were recorded. Extract showed 71% antioxidant activity. Moreover, the HPLC‐MS/MS detection revealed the presence of 18 compounds including P‐coumaric acid and antioxidants flavonoids, of those are seven compounds not previously detected in this species. The in vivo study showed a remarkable skin and hair pigmentation effect on plant extract‐treated groups, compared to the reference, placebo, and control groups. Histopathological examinations showed the growth of colored hair follicles in the dermis and epidermis layers of the extract‐treated mice. Conclusion: The study suggests the use of M. sativa extract in enhancing the pigmentation process in hypopigmented skin and hair if combined with UVA light. Therefore, M. sativa extract can be considered a potential treatment for vitiligo.